Washington connection and the third world fascism: the political economy of human rights volume1 - Chomsky, Noam; Herman, Edward S. (London, 2015)
The Political Economy of Human Rights is an important two volume work, co-authored with Edward Herman - also co-author of the classic Manufacturing Consent - which provides a complete dissection of American foreign policy during the 1960s and '70s, looking at the entire sweep of the Cold War during that period, including events in Vietnam, Cambodia, Indonesia and Latin America. For those looking to develop a broad understanding of American foreign policy during the 20th Century this work has been a vital resource and is now available to a new generation of scholars and activists.
Keywords: Diplomatic relations